PENERAPAN ARSITEKTUR EKOLOGI PADA OBJEK WISATA EDUKASI PETERNAKAN KAMBING ETAWA DI KALIGESING, PURWOREJO - Wulan Ratnaningsih; Wiwik Setyaningsih; Maya Andria (Universitas Sebelas Maret Surakarta, 2017)
Abstract : In this era of globalization, the tourism industry is the largest contributing are in various countries in the world. The absorption of the tourism industry on employment until the year 2020, more than 10%, 11% of the Global GDP, and total activity of tourist travel is projected to continue to rise to 16 billion (Speirs,2010 in Setyaningsih,2017). Indonesia is a country that has various potential nature, flora, fauna and culture that can be processed for attracting tourists. Purworejo has a potential offauna typical of the area in the form of Etawa Goat Kaligesing already known excellence quality of milk up to the many goats are exported to foreign countries such asMalaysia and Singapore. But it turns out that the existence of Etawa Goat Kaligesing not yet received special attention from the local community so many seeds out of the export practices of the country which caused the depletion of the number of seeds in etawa goat kaligesing his own origins. Based on existing problems, it takes a vessel that can accommodate the goat farm activities as etawa preservation of seedsas well as educational activities to society about the benefits and importance of preserving seeds etawa goat. To support the activities of animal husbandry and education in order to continue to be sustainable, then the activity last packed in tourism activities where the concept of designing attractions of yesteryear is by paying attention to the preservation of the surrounding environment, i.e. with the approach of Ecological Architecture. Keywords: Tourism, Etawa Goat, Farm, Ecological Architecture, and Educational Tours.